2006
DOI: 10.1007/s00383-006-1672-1
|View full text |Cite
|
Sign up to set email alerts
|

Late complications of circumcision in Iran

Abstract: Today, circumcision is the most commonly performed surgical procedure worldwide. Early and late complications may occur due to circumcision. To find the prevalence of late complications of circumcision, we studied 3,205 elementary-school boys aged 6-12 years in 2002. All of them were Iranian and Muslim. Nearly 3,125 of the boys have been circumcised. Most of the boys (2,214 boys) had been circumcised after 2 years of age. Moreover, most of them were operated by traditional circumcisers (43.49%). Late complicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
2
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 16 publications
4
51
2
2
Order By: Relevance
“…An Iranian cross-sectional study with good evidence reported a late complication rate of 7.4%, including redundant skin in 3.6%, excessive skin removal in 1.3%, and meatal stenosis in 0.9%. 197 …”
Section: Post-newborn Circumcisionmentioning
confidence: 99%
“…An Iranian cross-sectional study with good evidence reported a late complication rate of 7.4%, including redundant skin in 3.6%, excessive skin removal in 1.3%, and meatal stenosis in 0.9%. 197 …”
Section: Post-newborn Circumcisionmentioning
confidence: 99%
“…[1,2] On the other hand, glandular amputation, urethrocutaneous fistula, transmission of infections and uncontrolled hemorrhage are unacceptable complications of circumcision. [5][6][7] In Sub-Saharan Africa, all male children are routinely circumcised. Majority of circumcisions are performed during the neonatal period, except on health grounds.…”
Section: Introductionmentioning
confidence: 99%
“…These brought into question the rationale for circumcision, which resulted in a tilt towards "no circumcision" in many highly developed cultures. [5][6][7][8][9] Although circumcision is regarded as very common in this subregion, there are not many studies on the prevalence of, and factors influencing, circumcision mishaps in our setting.…”
Section: Introductionmentioning
confidence: 99%
“…The adverse effects of circumcision as a surgical procedure are much discussed and are regarded by some in the current debates as of importance, [17][18][19][20] but often as the only consequence of concern and one amenable to clinical management. Others see effects on sexual lives, pleasures, relations, meanings and cultures.…”
mentioning
confidence: 99%